Inactivation of uptake hydrogenase leads to enhanced and sustained hydrogen production with high nitrogenase activity under high light exposure in the cyanobacterium Anabaena siamensis TISTR 8012 - Khetkorn Wanthanee (Journal of Biological Engineering, 2012)
Abstract Background Biohydrogen from cyanobacteria has attracted public interest due to its potential as a renewable energy carrier produced from solar energy and water. Anabaena siamensis TISTR 8012, a novel strain isolated from rice paddy field in Thailand, has been identified as a promising cyanobacterial strain for use as a high-yield hydrogen producer attributed to the activities of two enzymes, nitrogenase and bidirectional hydrogenase. One main obstacle for high hydrogen production by A. siamensis is a light-driven hydrogen consumption catalyzed by the uptake hydrogenase. To overcome this and in order to enhance the potential for nitrogenase based hydrogen production, we engineered a hydrogen uptake deficient strain by interrupting hupS encoding the small subunit of the uptake hydrogenase. Results An engineered strain lacking a functional uptake hydrogenase (∆hupS) produced about 4-folds more hydrogen than the wild type strain. Moreover, the ∆hupS strain showed long term, sustained hydrogen production under light exposure with 2–3 folds higher nitrogenase activity compared to the wild type. In addition, HupS inactivation had no major effects on cell growth and heterocyst differentiation. Gene expression analysis using RT-PCR indicates that electrons and ATP molecules required for hydrogen production in the ∆hupS strain may be obtained from the electron transport chain associated with the photosynthetic oxidation of water in the vegetative cells. The ∆hupS strain was found to compete well with the wild type up to 50 h in a mixed culture, thereafter the wild type started to grow on the relative expense of the ∆hupS strain. Conclusions Inactivation of hupS is an effective strategy for improving biohydrogen production, in rates and specifically in total yield, in nitrogen-fixing cultures of the cyanobacterium Anabaena siamensis TISTR 8012.